Comparison of the antiemetic effectiveness between granisetron and dexamethasone with ondansetron and dexamethasone in acute-phase chemotherapy patients - Arfiani, Ria Fitrah; Susilo, Dwi Hari; Suprapti, Budi (Folia Medica Indonesiana, 2017)
Nausea and vomiting may occur in patients receiving chemotherapy, a condition referred to as chemotherapy-induced nausea and vomiting. The provision of combined dexamethasone and ondansetron or granisetron is the therapeutic management of acute phase nausea and vomiting in cytostatics with a high risk of nausea and vomiting. Granisetron has been known to have better pharmacokinetics and pharmacodynamics compared to ondansetron, so it is possible to have nausea and vomiting suppressing effect higher than that of ondansetron. This study aimed to compare antiemetic effectiveness of granisetron and dexamethasone with ondansetron and dexamethasone in acute-phase chemotherapy patients. This study was conducted in patients who received the combination of cisplatin-paclitaxel and cisplatin-fluorouracil, double-blind, with samples comprised new head and neck surgical oncology patients. Measurement of nausea and vomiting during the acute phase of chemotherapy was conducted using Index of Nausea, Vomiting, and Retching (INVR). Observation of nausea and vomiting in the patients was done during the first 12 hours after administration of cisplatin and interviews were conducted on h 12. Results showed that there was no difference in the effectiveness of nausea and vomiting suppression in the administration of granisetron and dexamethasone compared to ondanstron and dexamethasone in acute phase chemotherapy patients (p = 0.076).